2018
DOI: 10.1075/jlp.17043.ore
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the representation of refugees, asylum seekers and migrants in the Irish and UK press

Abstract: Coverage of migration in the media intensified during 2015 against the backdrop of a largescale European refugee crisis. Using corpus linguistics and critical discourse analysis, we explore the representation of refugees, asylum seekers, immigrants and migrants from September to November 2015, in UK and Irish newspapers. Data was collected from Nexis, using the Baker et al. (2008) RASIM framework. Using corpus linguistic techniques, we identify how these groups are represented, before drawing on CDA to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…O'Regan and Riordan (O'Regan, Riordan, 2018) explore the portrayal of refugees, asylum seekers, immigrants and migrants from September to November 2015, in UK andIrish newspapers. Felberg andŠarić (Felberg, Šarić, 2017) investigate the image of migration and migrants in Croatian and Serbian public broadcasters' online portals during the "migrant crisis" in 2015/2016.…”
Section: Discussionmentioning
confidence: 99%
“…O'Regan and Riordan (O'Regan, Riordan, 2018) explore the portrayal of refugees, asylum seekers, immigrants and migrants from September to November 2015, in UK andIrish newspapers. Felberg andŠarić (Felberg, Šarić, 2017) investigate the image of migration and migrants in Croatian and Serbian public broadcasters' online portals during the "migrant crisis" in 2015/2016.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ‘Otherness’ of refugees was highlighted by Bulgarian media (Kamenova, 2014), Slovenian tabloids (Vezovnik, 2017) and some British newspapers (Wilmott, 2017). Their conception as a threat and an economic burden was stressed in the Finnish (Järvinen, 2015), Austrian (Greussing and Boomgaarden, 2017), British (Gabrielatos and Baker, 2006; O’Regan and Riordan, 2018), Spanish (Durán, 2013) and Hungarian press (Vicsek et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berry et al (2016) investigated the coverage of refugees in five European countries in 2014 and 2015 1 and reported that, while their most positive depiction occurred in Swedish newspapers, variations were particularly evident in German and British press. More recently, O’Regan and Riordan (2018) compared their representations in Irish and UK press and found that the latter tends to focus on the need to remove failed asylum seekers, while the former considers them victims. Overall, a shift towards more humanitarian perspectives on refugees in international news discourse has only recently become visible, and so far relatively few studies have focused on this trend (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations